IMPACT OF SPATIAL VARIABILITY IN MICROFABRICS ON HEAT TRANSFER CHARACTERISTICS OF SOME SEDIMENTARY ROCKS - Padmanabhan, Eswaran (2010)
Heat flow studies in geological systems are of paramount interest to the oil and gas industry. Such studies give an indication on the thermal maturity of the hydrocarbon reserves and also provide a better enhanced understanding of the reservoir. The ongoing study on the geological Formations in Northern Sarawak has indicated the need to reevaluate the heat flow characteristics of the sedimentary rocks in the area. This need was a direct manifestation of strong discrepancies between the results and trends published by previous workers in the region. The Belait Formation adjacent to the Brunei border in North-eastern Sarawak has several oil wells and shows tremendous spatial variability that needs to be taken into account in reservoir characterization. Several sedimentation facies types were identified in the field. Several samples were selected from SK333 block for this study. The results indicate that heat transfer in clastics appears to be proportional to carbon contents and percentage of argillaceous material in the system. There appears to be an inverse relationship between the presence of Fe-oxyhydroxides in the matrix and heat transfer capabilities. In the non-clastics, certain facies such as the gray micritic facies appear to have high heat transfer capabilities. The transfer capability reduces from the carbonaceous to ferruginous varieties. Complex heterogeneity in fabric as seen in the fossiliferous varieties tends to lower the thermal conductivity to values as low as 3 Wm-1K-1. Normally specimens are selected to represent the cored geological sections from which they come. However, as the results of this study show that microvariability in fabrics is a dominant feature in these rocks, it is evident that utilizing such samples as representative samples for the overall geological formation could result in erroneous interpretations.